2015
DOI: 10.1099/ijsem.0.000552
|View full text |Cite
|
Sign up to set email alerts
|

Kutzneria chonburiensis sp. nov., isolated from soil

Abstract: A novel actinomycete strain, SMC 256 T , which developed small, globose sporangia at the ends of long sporangiophores on aerial mycelium, was isolated from soil collected in a mountain forest of Thailand. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain SMC 256 T belonged to the genus Kutzneria, and the closest phylogenetically related species were Kutzneria buriramensis BCC 29373 T (98.9 % 16S rRNA gene sequence similarity), Kutzneria kofuensis ATCC 27102 T (98.2 %), Kutzneria albi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…On the basis of the large 3 J H,H coupling constants (Table ) and NOESY correlations within each monosaccharide, Acu-A and Acu-B were identified as β-quinovose residues, while Acu-C was identified as the amino sugar β-acosamine (Figure S4). Thus, this trisaccharide was found to be identical to aculexitriose, previously found in aculeximycin (Figure ). An additional 3-amino-2,3-6-trideoxy-3-methylhexose unit comprising C1′′–C7′′ was constructed based on 2D NMR data (Figure ) and determined to be α-vancosamine based on the 3 J H,H coupling constants and the NOE cross-peaks (Figure S8a).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…On the basis of the large 3 J H,H coupling constants (Table ) and NOESY correlations within each monosaccharide, Acu-A and Acu-B were identified as β-quinovose residues, while Acu-C was identified as the amino sugar β-acosamine (Figure S4). Thus, this trisaccharide was found to be identical to aculexitriose, previously found in aculeximycin (Figure ). An additional 3-amino-2,3-6-trideoxy-3-methylhexose unit comprising C1′′–C7′′ was constructed based on 2D NMR data (Figure ) and determined to be α-vancosamine based on the 3 J H,H coupling constants and the NOE cross-peaks (Figure S8a).…”
Section: Resultssupporting
confidence: 77%
“…Another example of an underexplored genus within Actinobacteria is Kutzneria , which belongs to the Pseudonocardiaceae family . At present, only five species of this genus have been reported: Kutzneria viridogrisea , Kutzneria albida , Kutzneria kofuensis , Kutzneria buriramensis , and Kutzneria chonburiensis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kutzneria chonburiensis strain SMC256 T was isolated and taxonomically identified as described previously 39 . Briefly, it was isolated from a soil sample collected in a mountain forest in Chonburi province, Thailand.…”
Section: Methodsmentioning
confidence: 99%
“…One siderophore, one melanin, one lanthipeptide, Table 1. Phenotypic characteristics of strain AN110305 T and related species of the family Pseudonocardiaceae Taxa: 1, strain AN110305 T ; 2, Goodfellowiella [21,22]; 3, Umezawaea [53,54]; 4, Kutzneria [55][56][57][58]; 5, Saccharothrix [59][60][61][62][63][64]. Data were from this study unless indicated.…”
Section: Whole Genome Sequence Analysismentioning
confidence: 99%